Identifying Generational Gaps in Emotional Expression among Youth and Parents - Sharma, Neha; Bennett, Laura (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and interpret generational differences in emotional expression between youth and parents, focusing on how social, cognitive, and cultural factors influence emotional communication patterns across generations. Methods and Materials: This qualitative research employed an exploratory design grounded in the interpretivist paradigm to capture the lived experiences of emotional communication within families. The study involved 20 participants from Canada, comprising 10 youth (aged 18–25) and 10 parents (aged 40–60), selected through purposive sampling to ensure diversity in gender, culture, and socioeconomic background. Semi-structured interviews were conducted in person and online, each lasting 45–70 minutes, until theoretical saturation was reached. Data were transcribed verbatim and analyzed thematically using NVivo 14 software. Thematic analysis followed Braun and Clarke’s six-step framework, with codes and categories refined through constant comparison and reflexive journaling to ensure credibility and consistency. Findings: Five major themes emerged: (1) Communication Styles Across Generations, reflecting youth’s verbal openness versus parental restraint; (2) Technological Mediation of Emotion, highlighting digital communication as both a bridge and barrier; (3) Emotional Norms and Cultural Expectations, emphasizing the impact of cultural scripts and gendered expression; (4) Perceptions of Empathy and Understanding, revealing emotional misattunement and validation gaps; and (5) Adaptation and Emotional Bridging Mechanisms, showing efforts toward intergenerational empathy and emotional literacy. The findings indicated that differences in emotional vocabulary, digital fluency, and cultural norms contribute to misinterpretations and emotional distance, while reflective dialogue and hybrid communication foster improved understanding. Conclusion: Generational gaps in emotional expression arise from interwoven social, cultural, and cognitive mechanisms that shape emotion socialization within families. Promoting emotional literacy, reciprocal empathy, and adaptive communication practices can enhance intergenerational cohesion and emotional well-being.